EMOTIONAL CONFLICT OF RILEY IN INSIDE OUT (2015): A LITERARY PSYCHOLOGY STUDY - Giovanni Goh; Miduk Punguan Simangunsong; Aditiya Mulya Syarif; Stephani Anastasia; Chesya Purba (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
Emotions play a crucial role in human life as they influence the way individuals think, feel, and develop. However, studies that examine emotional conflict in animated films through a literary psychology perspective remain limited. This study analyzes the emotional conflict experienced by Riley, the protagonist of Inside Out (2015), focusing on the interactions among her core emotions: Joy, Sadness, Fear, Anger, and Disgust. Using a qualitative descriptive method, the analysis explores how the film represents Riley’s emotional struggles as she undergoes significant life changes, particularly her relocation to a new city and adaptation to an unfamiliar environment. The findings reveal that Riley’s emotional conflict reflects common psychological challenges faced by children in understanding and balancing their emotions. The film emphasizes the importance of both positive and negative emotions in personal growth, adaptation, and self-understanding. In conclusion, Inside Out not only offers an engaging narrative but also provides meaningful insight into emotional development and identity formation through the lens of literary psychology.